A quasi-experimental evaluation of an intervention to increase palliative medicine referral in the emergency department. Issue 3 (July 2019) - Tiernan, Eoin; Ryan, John; Casey, Mary; Hale, Aine; O'Reilly, Valerie; Devenish, Millie; Whyte, Barbara; Hollingsworth, Siobhan; Price, Olga; Callanan, Ian; Walsh, Declan; Normand, Charles; et al.
Objective: To evaluate a new intervention intended to increase referral rates from the emergency department (ED) to the palliative medicine service (PMS) in acute hospitals. Methods: We conducted a quasi-experimental evaluation in an urban teaching hospital in Dublin, Ireland. Data were collected over two eight-week periods in November/December 2013 and May/June 2015, with the PALliative Medicine in the Emergency Department (PAL.M.ED.™) intervention implemented in the intervening period. All adults who were admitted to the hospital via the ED during the two time periods and who received a palliative care consultation during their hospital stay were included in the study. Our primary analysis evaluated the impact of PAL.M.ED.™ on PMS referral in the ED. Our secondary analysis evaluated the impact of PMS referral in the ED on length of stay (LOS) and utilization, compared to PMS referral later in the admission. We controlled for observed confounding between groups using propensity scores. Results: PAL.M.ED.™ was associated with an increase in PMS referral in the ED ( p < 0.005; odds ratio: 10.5 (95%CI: 3.8 to 28.7)). PMS referral in the ED was associated with shorter hospital LOS ( p < 0.005; −10.9 days (95%CI: −17.7 to −4.1)). Conclusions: Low PMS referral rates in the ED, and the poor outcomes for patients and hospitals that arise from admissions of those with serious illness, may be mitigated by a proactive intervention to identify appropriate patients at admission.